Soldier Death Autopsies in Bursa - Türkmen, Nursel; Fedakar, Recep; Eren, Bülent; Durak, Dilek; Çoltu, Atınç (The Bulletin of Legal Medicine, 2006)
Military service has a significant role with respect to physical and psychological stress. Various medicolegal problems or deaths occur among soldiers due to different factors in different countries. In this study we aimed to investigate soldier deaths autopsied in 5 years in Bursa in different aspects and to emphasize their medicolegal dimension. Records of 3065 autopsy cases in Forensic Medicine Council Bursa Chairmanship were reviewed retrospectively and identified 39 soldier death cases were investigated in different aspects. The cases were all male, most common at the age of 21 years, and suicide was the main manner of death in 46.15% of cases. Autopsy and routine postmortem procedures are necessary to find out accurate and detailed data about soldier deaths to guide further studies to detect risk factors and to establish preventive strategies. Key words: Soldier, death, autopsy